Evaluation on effect of two plant extracts of Fumaria parviflora and Teucrium polium and releasing green lacewing compared with pesticides pymetrozin to control sweetpotato whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae) - M. A. Samih; M. Haghani; H. Sharifi (نامه انجمن حشره‌شناسی ایران, 2014)
The sweetpotato whitefly, Bemisia tabaci Genn. (Hemoptera: Aleyrodidae) is a worldwide economic pest both in the field and in the greenhouse. In this study, the efficiency of plant extracts of Fumaria parviflora (Lam.) (Fumariaceae) and Teucrium polium (L.) (Lamiaceae) and release of green lacewing Chrysoperla carnea (Steph.) eggs were compared with pymetrozin pesticide to control this pest in semi-field conditions. LC50 of plant extracts and pesticide for sweet potato whitefly were calculated by bioassay test. In the original experiment, plant extracts and pesticides were sprayed on tomato plants in cages that were covered with mesh fabric. Cardboard chamber containing lacewing eggs was hanged to plant tomatoes. Various days after applying control methods, sweetpotato whitefly populations were counted. The experiments were carried out at 25 ±5 °C , 50±5 RH and photoperiodism of 16:8 h (L:D). T. polium and F. parviflora extracts and pymtrozin LC50 was respectively 82.629, 23.002 and 0.118 mg/ml. Comparison of different control methods efficacy indicated efficacy of F. parviflora and T. polium extracts, pymetrozin and green lacewing was respectively 86.91, 83.51, 84.29 and 54.26 percent to control egg stage, 81.39, 79.68, 78.05 and 52.40 percent in controlling nymphal stage, 82.76, 77.31, 78.12 and 44.99 percent to control total immature stages and 83.01, 81.07, 79.00 and 64.20 in controlling of total nymphal stages. Results of efficacy experiments could be an introduction for further studies to replace the herbal extract rather than chemical pesticides in natural conditions.